Observations of stratospheric sudden warmings in Earth rotation variations. Issue 16 (19th August 2014) - Neef, Lisa; Walther, Sophia; Matthes, Katja; Kodera, Kunihiko
Abstract Stratospheric sudden warmings (SSWs) are extreme events in the polar stratosphere that are both caused by and have effects on the tropospheric flow. This means that SSWs are associated with changes in the angular momentum of the atmosphere, both before and after their onset. Because these angular momentum changes are transferred to the solid Earth, they can be observed in the rate of the Earth's rotation and the wobble of its rotational pole. By comparing observed Earth rotation variations to reanalysis data, we find that an anomaly in the orientation of the Earth's rotational pole, up to 4 times as large as the annual polar wobble, typically precedes SSWs by 20–40 days. The polar motion signal is due to pressure anomalies that are typically seen before SSW events and represents a new type of observable that may aid in the prediction of SSWs. A decline in the length of day is also seen, on average, near the time of the SSW wind reversal and is found to be due to anomalous easterly winds generated in the tropical troposphere around this time, though the structure and timing of this signal seems to vary widely from event to event.